2002
DOI: 10.1002/psc.407
|View full text |Cite
|
Sign up to set email alerts
|

Systematic optimization of a lead‐structure identities for a selective short peptide agonist for the human orphan receptor BRS‐3

Abstract: The orphan receptor, human bombesin receptor subtype 3 (BRS-3) was assigned to the G-protein coupled bombesin receptor family because of its high sequence homology with the neuromedin B receptor (NMB-R) and gastrin-releasing peptide receptor (GRP-R). Since its pharmacology is stiIl unknown, new highly potent and selective tool-substances are needed, that may be able to elucidate its possible role in obesity and cancer. We have performed structure activity relationship studies on the high affinity peptide agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…Molecular modeling demonstrated that these two selective BB 3 receptor ligands had a unique conformation of the position of the 11␤-amino acids, which probably accounted for their selectivity (Mantey et al, 2001). In a second study ]bombesin 6 -14 retained high affinity for the BB 3 receptor and was 227-fold more selective for the BB 3 receptor than for the human BB 2 receptor and 800-fold more selective than the human BB 1 receptor Weber et al (2002), and 3-phenylpropionyl-Ala,DTrp,NH(CH 2 ) 2 C 6 H 5 , compound 17d in Weber et al (2003)] were found (Mantey et al, 2006) in binding studies and studies of potency for activation of phospholipase C to have affinities Ͼ5 M for all three human bombesin receptor subtypes and therefore not to be useful. The novel compound Ac-Phe,Trp,Ala,His(tBzl), Nip,Gly,Arg-NH 2 [compound 34 in Boyle et al (2005)] had 14-and 20-fold higher affinities for the BB 3 receptor than for the BB 1 receptor BB 2 receptor, respectively (Mantey et al, 2006); however, its selectivity for the BB 3 receptor was less than that of [D-Tyr 6 ,Apa-4Cl 11 ,Phe 13 ,Nle 14 ]-bombesin 6 -14 (i.e., Ͼ100 fold selectivity) (Mantey et al, 2006) (Table 2).…”
mentioning
confidence: 95%
“…Molecular modeling demonstrated that these two selective BB 3 receptor ligands had a unique conformation of the position of the 11␤-amino acids, which probably accounted for their selectivity (Mantey et al, 2001). In a second study ]bombesin 6 -14 retained high affinity for the BB 3 receptor and was 227-fold more selective for the BB 3 receptor than for the human BB 2 receptor and 800-fold more selective than the human BB 1 receptor Weber et al (2002), and 3-phenylpropionyl-Ala,DTrp,NH(CH 2 ) 2 C 6 H 5 , compound 17d in Weber et al (2003)] were found (Mantey et al, 2006) in binding studies and studies of potency for activation of phospholipase C to have affinities Ͼ5 M for all three human bombesin receptor subtypes and therefore not to be useful. The novel compound Ac-Phe,Trp,Ala,His(tBzl), Nip,Gly,Arg-NH 2 [compound 34 in Boyle et al (2005)] had 14-and 20-fold higher affinities for the BB 3 receptor than for the BB 1 receptor BB 2 receptor, respectively (Mantey et al, 2006); however, its selectivity for the BB 3 receptor was less than that of [D-Tyr 6 ,Apa-4Cl 11 ,Phe 13 ,Nle 14 ]-bombesin 6 -14 (i.e., Ͼ100 fold selectivity) (Mantey et al, 2006) (Table 2).…”
mentioning
confidence: 95%
“…We have reported previously that the Bn analog [D-Phe 6 ,␤-Ala 11 ,Phe 13 ,Nle 14 ]Bn(6 -14) ( Table 1, Peptide 2), has high affinity for all known Bn receptors (Mantey et al, 1997(Mantey et al, , 2001Pradhan et al, 1998;Ryan et al, 1998a;Katsuno et al, 1999). Recently, analogs of [D-Phe 6 ,␤Ala 11 ,Phe 13 ,Nle 14 ]Bn(6 -14) have been described (Darker et al, 2001;Mantey et al, 2001Mantey et al, , 2004Weber et al, 2003Weber et al, , 2002 that are reported to have selectivity for hBRS-3 or the other Bn receptor subtypes. In three studies (Weber et al, 2002(Weber et al, , 2003Boyle et al, 2005), this selectivity was based on assessment of changes in [Ca 2ϩ ] i using a FLIPR assay with no direct assessment of receptor affinities.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, analogs of [D-Phe 6 ,␤Ala 11 ,Phe 13 ,Nle 14 ]Bn(6 -14) have been described (Darker et al, 2001;Mantey et al, 2001Mantey et al, , 2004Weber et al, 2003Weber et al, , 2002 that are reported to have selectivity for hBRS-3 or the other Bn receptor subtypes. In three studies (Weber et al, 2002(Weber et al, , 2003Boyle et al, 2005), this selectivity was based on assessment of changes in [Ca 2ϩ ] i using a FLIPR assay with no direct assessment of receptor affinities. In the present study, we have used a number of strategies known to produce receptor subtype-selective analogs with other peptides to synthesize possible new analogs selective for human Bn receptor subtypes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations